Motivasi Belajar Dan Literasi Digital Sebagai Faktor Dominan Dalam Pencapaian Hasil Belajar Pada Pembelajaran TPAV - Muhammad Ilham Dhaifullah; Fitri Yanti (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
The use of digital technology in learning does not always lead to improved student learning outcomes, making it important to identify the factors that contribute to learning achievement in technology-based learning. This study aims to analyze the role of digital literacy and learning motivation in students' learning outcomes in the Audio Video Processing Engineering (TPAV) subject. The study employed a quantitative approach using a causal associative research design. The entire population of 28 students majoring in Visual Communication Design was selected as the sample through saturated sampling. Data were collected using digital literacy and learning motivation questionnaires, as well as a learning achievement test, and were analyzed using multiple linear regression. The results showed that digital literacy had no significant effect on learning outcomes (sig. 0.128), while learning motivation had a positive and significant effect (sig. <0.001). Simultaneously, digital literacy and learning motivation had a significant effect on learning outcomes, with a contribution of 76.8%. Thus, learning motivation was found to be the more dominant factor in students' learning achievement, while digital literacy provides greater benefits when supported by strong learning motivation.   Keywords: Digital Literacy; Learning Motivation; Learning Outcomes; Vocational Education